Immigrants and welfare receipt in Ireland - Alan Barrett; Corona Joyce; Bertrand Maître (Institute for the Study of Labor (IZA), 2011)
Since 2004, Ireland has included in its system of social welfare payments criteria for receipt which limit the extent to which immigrants can receive welfare payments. In this paper, we compare the rates of receipt of welfare for immigrants and natives to see if the outcome is consistent with the operation of this policy. Using data from 2008, we generally find lower rates of welfare receipt among immigrants. While the numbers of immigrants claiming unemployment-related payments surged at the outset of the recession, there appears to have been a quicker stabilisation in the number of immigrants claiming such benefits relative to natives, based on official data from 2007 to 2010. This would be consistent with the on-going implementation of the type of criteria introduced in 2004.
urn:nbn:de:101:1-201104113895
Keywords: I38; J61; 330; Ireland; immigrants; welfare; Migranten; Sozialhilfeempfänger; Arbeitslosenversicherung; Vergleich; Bevölkerung; Irland